Democratising Nuclear Governance: The Role of African Civil Society in the International Campaign to Abolish Nuclear Weapons (ICAN) - Michaelan Sinnett; Joelien Pretorius (The Thinker)
The entry into force of the Treaty on the Prohibition of Nuclear Weapons (TPNW) on 22 January 2021 presented a turn in nuclear politics. It is a unique instrument in the governance of nuclear weapons, because its advocacy was led and managed by non-nuclear weapon states and transnational civil society organisations. It is widely acknowledged that transnational civil society plays a democratising role in international governance and that the International Campaign to Abolish Nuclear Weapons (ICAN) did exactly that for nuclear governance through its facilitation of the Humanitarian Initiative that unfolded into the negotiation of the TPNW. This article elaborates on this role, guided by Scholte’s (2002) framework of the assessment of transnational civil society’s democratising role in global governance, to map ICAN’s role in six criteria: awareness, participation, contestation, transparency, accountability, and legitimacy. However, the extent of broad-based representation of civil societies across the world is equally important to ICAN’s role. It is in this respect that the article turns specifically to African civil society participation as part of ICAN. Although several African civil society organisations partnered with ICAN, the question goes beyond the quantitative side of their participation, to its quality. Although challenges were experienced in the leadership and decision-making structures around racial and regional diversity, African campaigners see their role in ICAN as transformative and empowering.